Pengukuran Efisiensi Kinerja Komoditi Industri Sandang Kabupaten Agam Menggunakan Data Envelopment Analysis (DEA) - Rahmatika Rahmatika; Dewi Murni; Yerizon Yerizon (UNIVERSITAS NEGERI PADANG, 2019)
Abstract –Clothing industry is the dominant industry inAgam. The performance of the commodities industry clothing can be determined from input and output factors. The measurement of efficiency is a way to see just how efficient use of inputs and outputs. All this time, it has not been done the measurement of efficiency of the performance of clothing industries in Agam. The measurement of the efficiency of the performance of the industries clothing agam purpose to look at the commodities industry efficient or inefisien. The measurement of efficiency can be using by the method of DEA using CRS and VRS model. For a DMU inefisien can be done by doing a calculation DMU improvement targets that leverages the value of slack. The calculation of the value of the target will be the calculation of the efficiency of the back which resulted in the DMU inefisien be efficient.Keywords – Data Envelopment Analysis, DEA CRS, DEA VRS, Slack, Target.